Is Language the Result of a Necessity? - Franca Daniele (European Scientific Journal, ESJ, 2017)
One of the most human characteristics is certainly language. Language is the means through which people communicate with each other both orally and in written form. Language represents one of the most important social behaviors, and thanks to language humans have been able to accumulate knowledge and transmit it from one generation to the next. The present paper will analyze how the human body has changed and evolved in response to the environmental solicitations and stimuli that have given origin to the development of a structured language, and parallel this with how, in turn, medical language has changed in the past years in response to social and cultural modifications.